2007
DOI: 10.1088/1751-8113/40/38/007
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Lie derivative and μ-symmetries

Abstract: We introduce, in the spirit of Witten's gauging of exterior differential, a deformed Lie derivative that allows a geometrical interpretation of λand µ-symmetries, in complete analogy with standard symmetries. The case of variational symmetries (both for ODEs and for PDEs) is also considered in this approach, leading to λand µ-conservation laws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 22 publications
(59 reference statements)
0
40
0
Order By: Relevance
“…note that here the functions ρ i are arbitrary ones. If in addition the matrices Λ i are multiples of the identity, see (37), this reads…”
Section: Simple Twisted Symmetries: µ-Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…note that here the functions ρ i are arbitrary ones. If in addition the matrices Λ i are multiples of the identity, see (37), this reads…”
Section: Simple Twisted Symmetries: µ-Symmetriesmentioning
confidence: 99%
“…⊙ Remark 19. Here we are not discussing the relation of µ-prolongations and symmetries with µ-related deformed exterior and Lie derivatives; this point of view was advocated by Morando [37].…”
Section: Simple Twisted Symmetries: µ-Symmetriesmentioning
confidence: 99%
“…It can be shown that (20) has no point symmetries but admits a λ-covering with λ = xe x/u . Hence, if we consider the covering system E ′ defined by (20) together with w 1 = λ, it admits the nonlocal symmetry Y generated by ϕ 1 = e w u 2 /x and ϕ 2 = −e w .…”
Section: Remarkmentioning
confidence: 99%
“…Hence, if we consider the covering system E ′ defined by (20) together with w 1 = λ, it admits the nonlocal symmetry Y generated by ϕ 1 = e w u 2 /x and ϕ 2 = −e w . We will search for solvable structures which extend the nonabelian algebra G =< Y 1 = Y, Y 2 = ∂ w >.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation